Development of Interactive Science Problem Solver Media Based on PBL to Improve Collaboration Skills of Elementary School Students - Sitepu, Melyani Sari; Azizah, Azizah; Asriani, Asriani; Herlina, Herlina; Nuraini, Nuraini; Afifah, Mar’atul; Nur’izzani, Nur’izzani (Jurnal Paedagogy, 2025)
This study aims to develop interactive science problem solver media based on PBL for elementary school students to improve elementary school students' collaboration skills. The research method used is Research & Development (R&D) with the Sugiyono model. The subjects of the trial were students of class 5A phase C of SD Inpres Perumnas Palu City, Central Sulawesi. Data collection instruments used questionnaires, observations and interviews. Data analysis techniques used qualitative and quantitative analysis. The average validation results of media experts were 73.34% with a valid category, material experts 87.97% with a very valid category, language experts 92.98% with a very valid category, and content experts 100% with a very valid category. The results of the practicality test through student responses were 97.8% with a very practical category and teacher responses 97.5% with a very practical category. These results indicate that interactive multimedia is included in the very valid and very practical categories. The results of the interactive multimedia effectiveness test on students' collaboration skills using the Wilcoxon Signed test obtained a significance value of 0.005 <0.05, then accepting the Ha hypothesis and rejecting Ho. So it can be concluded that the interactive science problem solver media meets the criteria of being valid, practical, and effective in improving students' collaboration skills.